Insect-based novel food: is Italy ready for the food of the future? A survey on entomophagy among Italian people. - Buongiovanni, Roberta; Pisano, Maria Teresa; Spagnolo, Federica Maria Agata; Locorriere, Denny; Lorini, Chiara; Del Riccio, Marco; Bonaccorsi, Guglielmo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. According to the European Food Safety Authority (EFSA), novel food is defined as food that had not been consumed to a significant degree by humans in the EU before May 15th 1997, when the first regulation of novel food came into force. This study investigates the consumption of insect-based novel food in Italy, where cultural aversions and particular disgust are major barriers to acceptance.Methods. A cross-sectional study was conducted using a three-sections questionnaire shared through social media platforms (Facebook, Instagram, WhatsApp). The questionnaire explored socio-demographic characteristics, prior knowledge of novel food, willingness to consume insect-based food, and the impact of packaging on consumer choices. Frequencies for different items were calculated and reported in tables and charts.Results. The sample showed that the majority of respondents were female (56.3%) and aged 26-35 years (24.8%). Most participants were from Southern Italy (61.8%) and had a high school diploma (45.6%). However, the majority of novel food consumers appears to be male, less than 35 years-old and born in Northern Italy. Disgust is the main obstacle towards the consumption of insects (n=261, 78.4%) while, conversely, curiosity was also significant (72.9%). Packaging had a considerable influence on consumer choices: 74.1% were willing to try chips made from cricket flour, while only 15.0% were willing to try whole insects.Conclusion. Despite strong cultural barriers, strategies such as improved information and appealing packaging could increase acceptance of insect-based foods in Italy, particularly among younger, educated consumers.